Proceedings of the 40th Annual International Symposium on Computer Architecture 2013
DOI: 10.1145/2485922.2485960
|View full text |Cite
|
Sign up to set email alerts
|

Tri-level-cell phase change memory

Abstract: There are several emerging memory technologies looming on the horizon to compensate the physical scaling challenges of DRAM. Phase change memory (PCM) is one such candidate proposed for being part of the main memory in computing systems. One salient feature of PCM is its multi-level-cell (MLC) property, which can be used to multiply the memory capacity at the cell level. However, due to the nature of PCM that the value written to the cell can drift over time, PCM is prone to a unique type of soft errors, posin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…As stated before, MLC PCM suffers from several drawbacks. Recent studies in [51] showed that the drift problem might be so severe as to make MLC PCM infeasible. Thus, they proposed to remove the most vulnerable resistance level to drift, that is, the third level.…”
Section: Tri-level Write Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated before, MLC PCM suffers from several drawbacks. Recent studies in [51] showed that the drift problem might be so severe as to make MLC PCM infeasible. Thus, they proposed to remove the most vulnerable resistance level to drift, that is, the third level.…”
Section: Tri-level Write Modelmentioning
confidence: 99%
“…Another drawback of MLC PCM is its vulnerability to resistance drift, which is changing cell value based on increasing cell resistance over time. A recent study [51] proposed Tri-Level PCM to use three resistance levels (instead of four levels in a 2-bit MLC PCM) to increase the reliability and write speed. In Tri-Level PCM, the most vulnerable resistance level of MLC PCM to drift (i.e., the third level) is removed, leaving a wide resistance region between the second and fourth resistance levels.…”
mentioning
confidence: 99%
“…Seong et al proposed Tri-level cell of PCM and SAFER for stuck-at errors to achieve reliable memory system [34,33]. Schechter et al proposed ECP to replace ECC for resistive memory, in order to handle permanent errors [32].…”
Section: Related Workmentioning
confidence: 99%
“…Considering all these effects, we calculate the possibility of position errors based on 10 9 times Monte-Carlo simulation and its fitting curve, which is similar to the method used in [34]. In Figure 4, we present a probability distribution (PDF) of position errors for a single shift operation.…”
Section: Error Modelingmentioning
confidence: 99%
“…Seong et al proposed Tri-level cell of PCM and SAFER for stuck-at errors to achieve reliable memory system [34,33]. Schechter et al proposed ECP to replace ECC for resistive memory, in order to handle permanent errors [32].…”
Section: Related Workmentioning
confidence: 99%